Global tantra : religion, science, and nationalism in colonial modernity - Strube, Julian (New York: Oxford University Press, 2022)
"Beyond introducing the subject matter and critically surveying the state of scholarship, this introduction offers a substantial theoretical and methodological elucidation of the book's approach that is also relevant for readers not strictly interested in the specialized subject. Combining perspectives from religious studies, global history, South Asian studies, and the study of esotericism, the foundations of global religious history are discussed both in abstraction and in light of the source material. This especially considers historiographical challenges such as (post)colonialism, Eurocentrism, or Orientalism, as well as issues such as the blurry meaning of "global connections" and differentiations between the global, regional, and local. Leading themes such as the contested meaning of tradition, revival, reform, and modernity are scrutinized, as are the relationship and meanings of religion, science, esotericism, and nationalism that remain the subject of scholarly debate. Global religious history makes proposals for resolving such debates by eliding disciplinary boundaries"--
Includes bibliographical references and index.
Keywords: Tantrism -- India -- History; Science -- India; Political science -- India; India -- Intellectual life; India -- Religion